2012
DOI: 10.1002/pssc.201100557
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence study of e‐irradiated and plastically deformed ZnO crystals

Abstract: Intrinsic defects are generated by e‐irrradiation, and plastic deformation in ZnO crystals. Spectrally resolved cathodoluminescence (CL) experiments permit the analysis of the optical signature of those defects. We present herein a CL analysis of ZnO crystals irradiated with high energy electrons, and plastically deformed by Vickers indentation. Spectral changes around 3.3 eV and in the deep level emission are observed in the irradiated samples. These changes are compared to those observed around the extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…1(a) demonstrates that mechanical polishing creates high concentrations of V Zn -related defects within the outer $500 nm. This is consistent with recent PL 15 and PAS 19 measurements of mechanically polished ZnO, which showed the formation of vacancy type defects in the near surface region including V Zn . Previous CL and PL of ZnO showed that mechanical polishing leads to subsurface damage with NBE intensity decreases, 10,14,15 which our results confirm.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…1(a) demonstrates that mechanical polishing creates high concentrations of V Zn -related defects within the outer $500 nm. This is consistent with recent PL 15 and PAS 19 measurements of mechanically polished ZnO, which showed the formation of vacancy type defects in the near surface region including V Zn . Previous CL and PL of ZnO showed that mechanical polishing leads to subsurface damage with NBE intensity decreases, 10,14,15 which our results confirm.…”
supporting
confidence: 92%
“…This is consistent with recent PL 15 and PAS 19 measurements of mechanically polished ZnO, which showed the formation of vacancy type defects in the near surface region including V Zn . Previous CL and PL of ZnO showed that mechanical polishing leads to subsurface damage with NBE intensity decreases, 10,14,15 which our results confirm. The $2.05 eV emissions apparent for maximum range depths of $500 nm are also consistent with the depletion region measured by C-V previously of nearly 600 nm and with the acceptor nature of V Zn -related defects, which compensate the n-type doping.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…The accumulation of space charges might also be favorable in these directions. A relation between defects generated by electron irradiation and plastic deformation in ZnO crystals has been suggested [18]. Since localized charges in solids are closely related to excitons, cathodoluminescence microscopy of the nanostructured ZnO crystals could verify this hypothesis.…”
Section: Resultsmentioning
confidence: 96%